Maize miRNA and target regulation in response to hormone depletion and light exposure during somatic embryogenesis - Chávez-Hernández, Elva C.; Alejandri-Ramírez, Naholi D.; Juárez-González, Vasti T.; Dinkova, Tzvetanka D. (Frontiers in Plant Science, 2015)
Maize somatic embryogenesis is induced from the immature zygotic embryo in darkness and under the appropriate hormones’ levels. Small RNA expression is reprogrammed and certain miRNAs become particularly enriched during induction while others, characteristic to the zygotic embryo, decrease. To explore the impact of different environmental cues on miRNA regulation in maize somatic embryogenesis, we tested specific miRNA abundance and their target gene expression in response to photoperiod and hormone depletion for two different maize cultivars (VS-535 and H-565). The expression levels of miR156, miR159, miR164, miR168, miR397, miR398, miR408, miR528 and some predicted targets (SBP23, GA-MYB, CUC2, AGO1c, LAC2, SOD9, GR1, SOD1A, PLC) were examined upon staged hormone depletion in the presence of light photoperiod or darkness. Almost all examined miRNA, except miR159, increased upon hormone depletion, regardless photoperiod absence/presence. miR528, miR408 and miR398 changed the most. On the other hand, expression of miRNA target genes was strongly regulated by the photoperiod exposure. Stress-related miRNA targets showed greater differences between cultivars than development-related targets. miRNA/target inverse relationship was more frequently observed in darkness than light. Interestingly, miR528, but not miR159, miR168 or miR398, was located on polyribosome fractions suggesting a role for this miRNA at the level of translation. Overall our results demonstrate that hormone depletion exerts a great influence on specific miRNA expression during plant regeneration independently of light. However, their targets are additionally influenced by the presence of photoperiod. The reproducibility or differences observed for particular miRNA-target regulation between two different highly embryogenic genotypes provide clues for conserved miRNA roles within the SE process.